2022
DOI: 10.1126/sciadv.abq5295
|View full text |Cite
|
Sign up to set email alerts
|

Microscale mobile surface double layer in a glassy polymer

Abstract: This study examines the origin of the widely different length scales, h t —nanometers to micrometers—that have been observed for the propagation of the near-surface enhanced mobility in glassy polymers. Mechanical relaxations of polystyrene films with thicknesses, h , from 5 nm to 186 μm have been studied. For h < ~1 μm, the films relaxed faster than the bulk and the relaxation time decreased with decreasing h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(87 reference statements)
3
8
0
Order By: Relevance
“…2E). Similar double surface layers with an unexpectedly large thicknesses of more than 100 particles have recently been observed in glasses ( 27 , 44 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…2E). Similar double surface layers with an unexpectedly large thicknesses of more than 100 particles have recently been observed in glasses ( 27 , 44 ).…”
Section: Resultssupporting
confidence: 80%
“…2E). Similar double surface layers with an unexpectedly large thicknesses of more than 100 particles have recently been observed in glasses (27,44). d 1,2 represents the penetration depths of the surface effect on structure and dynamics, respectively.…”
Section: Slow Temperature Changesupporting
confidence: 74%
“…They 36 also found that before equilibrium was established, the local T g at a fixed distance from the interface decreased continuously with annealing. In this experiment, the preannealing temperature is below the T g surf of ∼350 K. However, we believe that interpenetration between the PS and PDMS chains at the PS-PDMS interface and hence interfacial broadening are probable because of the prolonged preannealing time used: The experimental time (t exp ) used here to measure the surface glass transition is 1800 s. According to Yuan et al, 73 the ratio of the surface relaxation time at 343 K to that at 350 K is ∼1.9. Therefore, at a preannealing temperature of 343 K, our films may undergo the surface glass transition at about 1800 s × 1.9 = 3420 s, which is much shorter than the preannealing time of 5 h used.…”
Section: Surface Glass Transition Of Thin Ps Filmsmentioning
confidence: 96%
“…Chen et al 72 monitored the rotational motion of single fluorescent probe molecules in poly(n-butyl methacrylate) films on glass coverslips under different residual stresses and found that the orientational relaxation time of the probe molecules (which manifests the segmental dynamics of the polymer) decreased by only 15% relative to that of the fully relaxed films even at a residual stress of more than ∼1 MPa. Based on the temperature dependence of the surface relaxation time of PS, 73 to produce a reduction in the T g surf from 355 to 325 K as shown in Figure 7a, the relaxation time should be reduced by a factor of ∼15. These observations indicate that the mobilityenhancing effect of residual stress on the films may be too small to account for the reductions in T g surf we observed.…”
Section: Surface Glass Transition Of Thin Ps Filmsmentioning
confidence: 99%
“…The past three decades have witnessed intense research focused on nanoscale confinement effects of polymeric glass-formers. Studies have reported that a broad range of properties, including the glass-transition temperature ( T g ), surface viscosity, small-mole...…”
Section: Introductionmentioning
confidence: 99%